Smell of green leaf volatiles attracts white storks to freshly cut meadows - Wikelski, Martin (Sci Rep, 2021)
Finding food is perhaps the most important task for all animals. Birds often show up unexpectedly at novel food sources such as freshly tilled fields or mown meadows. Here we test whether wild European white storks primarily use visual, social, auditory or olfactory information to find freshly cut farm pastures where insects and rodents abound. Aerial observations of an entire local stork population documented that birds could not have become aware of a mown field through auditory, visual or social information. Only birds within a 75° downwind cone over 0.4–16.6 km approached any mown field. Placing freshly cut grass from elsewhere on selected unmown fields elicited similarly immediate stork approaches. Furthermore, uncut fields that were sprayed with a green leaf volatile organic compound mix ((Z)-3-hexenal, (Z)-3-hexenol, hexenyl acetate), the smell of freshly cut grass, immediately attracted storks. The use of long-distance olfactory information for finding food may be common in birds, contrary to current perception.